2016
DOI: 10.1071/an15089
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of B-splines and non-linear functions to describe growth patterns and predict mature weight of female beef cattle

Abstract: The objective of this study was to compare the ability of Basis spline (B-spline) models and five non-linear functions (Richards, Brody, Von Bertalanffy, Gompertz and Logistic) to describe the growth of females of a beef cattle breed and predict cow mature weight (A). Random regression models that included animal variation within function parameters were fitted using mixed model procedures. Comparisons were made among these functions for goodness of fit, standardised residuals and biological interpretability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…In our study, after the first calving, the calf LW at birth and growth rate were not affected by the early nutritional treatment, suggesting that maternal nutrition did not affect the performance of this second generation, at least during lactation. However, since females of these breeds reach maturity when they are 4 to 5 years old [29], further studies are needed to determine if the heifer growth delay at weaning would impact the attainment of adult weight and mature size. Regarding breed, PA heifers had higher growth rates during rearing, BCS at calving, and calf LW at weaning than PI heifers, in accordance with previous studies [30], which evidenced similar interbreed differences.…”
Section: Growth Of Heifers and Their Calvesmentioning
confidence: 99%
“…In our study, after the first calving, the calf LW at birth and growth rate were not affected by the early nutritional treatment, suggesting that maternal nutrition did not affect the performance of this second generation, at least during lactation. However, since females of these breeds reach maturity when they are 4 to 5 years old [29], further studies are needed to determine if the heifer growth delay at weaning would impact the attainment of adult weight and mature size. Regarding breed, PA heifers had higher growth rates during rearing, BCS at calving, and calf LW at weaning than PI heifers, in accordance with previous studies [30], which evidenced similar interbreed differences.…”
Section: Growth Of Heifers and Their Calvesmentioning
confidence: 99%
“…Moreover, Miguel et al (2012) found that the Brody model was the best to estimate the actual weight at different ages in castrated Brahman males, although the Gompertz model showed the best overall fit. In a recent study by Gano et al (2015) on Parda de Montaña breed, the Richards function provided the best goodness of fit as also suggested by DeNise and Brinks (1985) and Doren et al (1989). Moreover, Gano et al (2015) reported that the von Bertalanffy function also described the dataset satisfactorily, whereas the logistic equation had the worst fit.…”
Section: Discussionmentioning
confidence: 65%
“…In a recent study by Gano et al (2015) on Parda de Montaña breed, the Richards function provided the best goodness of fit as also suggested by DeNise and Brinks (1985) and Doren et al (1989). Moreover, Gano et al (2015) reported that the von Bertalanffy function also described the dataset satisfactorily, whereas the logistic equation had the worst fit. Goldberg and Ravagnolo (2015) analyzed the growth curves for Angus cows using different nonlinear models and the results showed that the Richards model was the best to fit the data.…”
Section: Discussionmentioning
confidence: 65%
“…Jabres cattle have strong correlation among body size parameter in every group except female Jabres cattle same or above 1 years old. It can be happen because the cattle growth after 2 years old did not obey the linear curve (Gano et al 2015). The same condition also happen for Bali cattle (Ni'am et al 2012).…”
Section: Correlation Analysis Of Body Size Of Jabres Cattlementioning
confidence: 86%
“…Contrarily, the worst fit equation was obtained for female cattle with age same or above 1 years old. It can be happened because the growth of adult cattle after 2 years old is non-linear so the body weight prediction became harder (Gano et al 2015). The male cattle with age above 1 years only contained a few cattle with age above 2 years old, meanwhile the female cattle with age above 1aspects old contained many cattle with age above 2 years old.…”
Section: Regression Analysis Of Jabres Cattle Body Sizementioning
confidence: 99%